Detection and initial characterization of protein entities consisting of the HIV glycoprotein cytoplasmic C-terminal domain alone - Pfeiffer, Tanya; Ruppert, Thomas; Schaal, Heiner; Bosch, Valerie (Virology, 2013)
Employing antibodies against the cytoplasmic tail of the HIV-1 glycoprotein (Env-CT), in addition to gp160/gp41, we have identified several novel small Env proteins (<25kD) in HIV-1 transfected and infected cells. Mass spectrometric and mutational analyses show that two mechanisms contribute to their generation. Thus the protein, designated Tr-Env-CT (for truncated Env-CT), consists of the C-terminal 139 amino acids (aa) of Env (aa 718-856) with the N-terminal Q718 modified to pyroglutamic acid. It is likely derived from full-length Env protein by proteolytic processing. A further heterogeneous set of slightly larger proteins, termed Env-CT* species, are rather derived from spliced mRNAs containing only those Env C-terminal residues (aa 719-856) which overlap with the second tat and rev coding exons. They are N-terminally extended in the same reading frame. It is conceivable that essential Env-CT functions may be fulfilled by these novel species rather than by the full-length glycoprotein itself.
Gesehen am 20.01.2022